Pelatihan Pembuatan Media ‘Flip-Panel Numerasi Awal’ bagi Guru PAUD untuk Meningkatkan Pemahaman Konsep Penjumlahan Konkret Anak Usia 5-6 Tahun - Delvhina Manga; Herlina Herlina; Sri Rika Amriani; Fadhilah Afifah; Andi Nur Maharani Islami (Universitas Pahlawan Tuanku Tambusai, 2026)
This community service program aimed to improve the pedagogical competence and technical skills of early childhood education (ECE) teachers in Bajeng District, Gowa Regency, Sulawesi Selatan through training in developing “Flip-Panel Early Numeracy” learning media. The main challenge was the limited availability of systematic manipulative media for teaching concrete addition. The program involved 20 teachers and was conducted through a hands-on workshop, including concept reinforcement, demonstration, and guided practice in designing and assembling the media. Evaluation using pre-test and post-test showed a significant improvement, with average scores increasing from 43.8 to 86.0. The activity also resulted in the production of ready-to-use instructional media. The findings indicate that hands-on training effectively enhances teachers’ competence and promotes independence in developing learning tools. This initiative supports the implementation of the Merdeka Curriculum and contributes to achieving SDG 4 on quality education.